MEMAKNAI HAK DAN KEWAJIBAN DALAM KEBIJAKANKERJASAMA SWASTA DENGAN PEMERINTAH DAERAH(PEMDA) MELALUI PERJANJIAN BUILD OPERATE TRANSFER (BOT) BIDANG PASAR - Muhammad Dzikirullah H Noho (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
Rights and obligations in the Regional Government cooperation agreement with Swata can be seen from the balance of contract, the balance itself is the principle that requires both parties to fulfill and implement the agreement. This balance is important to build equality for the parties involved in relation to rights and obligations. However, interpreting this equality is still difficult. Both parties have their own interests. This study uses a qualitative method with an interpretive approach, where through this approach there is an emphasis to see one text relation with another text. Based on this approach, to illustrate the text in the policy of between cooperation regional government and the sector private in BOT contact, it can be done using the signifiying order and three-dimensional analysis triggered by Danesi and Perron. Understanding the rights and obligations of BOT contracts is seen as a reality both social and legal. This reality as a balancing ground operates a private cooperation agreement. Through the relationship between text as rights and texts as an obligation, it will be illustrated if the roles of the parties in private cooperation with the local government are mutually aware of their respective duties and functions.